(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The aim of this write up is to furnish nearly all elemental aspects on varied behavioral patterns along with different management strategies which may lead to an improvement in treatment planning and management by the dental practitioners, and comprehensive oral health care of the children suffering from Autism. Along with it, this article focuses on raising concerns among primary health care providers and parents of those children regarding there un-mate dental needs.